Pediatric meningioma: a clinicopathologic and molecular study with potential grading implications. (6th August 2020) - Toland, Angus; McNulty, Samantha N.; Pekmezci, Melike; Evenson, Michael; Huntoon, Kristin; Pierson, Christopher R.; Boue, Daniel R.; Perry, Arie; Dahiya, Sonika
Abstract: Meningiomas are common in adults ( 35% of brain tumors) but rare in children, where they exhibit unique clinical, pathological and molecular features compared to adult counterparts. Thus, data generated from adult cohorts may be imperfectly suited to guiding diagnostic, prognostic and treatment decisions for children. We studied 50 meningioma patients ≤18 years with available clinical and pathological data to address the need for data obtained in the pediatric setting. As previously described, we noted a slight bias toward male patients and a higher proportion of spinal tumors compared to adults. Thirty‐eight of 50 specimens were further analyzed by next generation sequencing. Loss‐of‐function mutations in NF2 and chromosome 22 losses were common, but pathogenic variants in other genes ( SMARCB1, FUBP1, BRAF, TERT promoter, CHEK2, SMAD and GATA3 ) were identified in a minority of cases. Copy number variants outside of chromosomes 22 and 1 were infrequent. H3K27 hypomethylation, a useful biomarker in adult tumors, was not found in our cohort. In exploring the correlation between mitotic count and recurrence‐free survival, we found a threshold of six mitoses per 10 high powered fields as the optimal cutoff in predicting recurrence‐free survival. If independently validated in larger studies, adjusted grading thresholds could enhance the clinical management of pediatric meningiomas.